2005
DOI: 10.1088/0954-3899/31/8/008
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent Green's function calculations of16O at small missing energies

Abstract: Calculations of the one-hole spectral function of 16 O for small missing energies are reviewed. The self-consistent Green's function approach is employed together with the Faddeev equations technique in order to study the coupling of both particle-particle and particle-hole phonons to the single-particle motion. The results indicate that the characteristics of hole fragmentation are related to the low-lying states of 16 O and an improvement of the description of this spectrum, beyond the random phase approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The LRC, describing the collective motion at low energy as well as the long-range part of TC, were computed using the self consistent Green's function (SCGF) formalism [2] in an appropriate harmonic oscillator basis. The effects of SRC due to the central and tensor part at high momenta were added by computing the appropriate defect functions.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The LRC, describing the collective motion at low energy as well as the long-range part of TC, were computed using the self consistent Green's function (SCGF) formalism [2] in an appropriate harmonic oscillator basis. The effects of SRC due to the central and tensor part at high momenta were added by computing the appropriate defect functions.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The two-nucleon overlap function (TOF) ψ i contains information on nuclear structure and correlations. For the case of proton-neutron emission from 16 O different approaches are used in [8,14,15] to calculate the TOF.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In the more sophisticated approach of [8], that we call SF-B, the TOF was computed partitioning the Hilbert space in order to determine the contribution of long-range correlations (LRC) and SRC separately. The LRC, describing the collective motion at low energy as well as the long range part of TC, were computed using the self-consistent Green's function formalism [16] in an appropriate harmonic-oscillator (h.o.) basis.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that it is necessary to include two-nucleon correlations beyond the mean field in order to describe some basic nuclear properties such as binding energy [1,2].…”
Section: Introductionmentioning
confidence: 99%